2021
DOI: 10.1177/21582440211067232
|View full text |Cite
|
Sign up to set email alerts
|

Which Service Attributes Sway Internet Service Providers? Analysis Through Triangulation Approach

Abstract: Internet service providing industry is considered a mainstay for all types of organizations all over the world. In order to be competitive, internet service providers (ISPs) need to realize that all service quality attributes do not carry the same value in customers’ eyes. Therefore, the present study proposes a rationally appealing methodological framework for prioritizing attributes of the SERVQUAL model without restricting them to their dimensions. The responses on 22 attributes of service quality collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Jönke (2012) concluded that the more customers use the Internet on a regular basis, the more they need and appreciate instant support. Adusei and Tweneboah-Koduah (2019) revealed that after-sales services influenced customer satisfaction in a positive direction so that the level of technical support activities employed by a business organization to a large extent determines the level of profit margin to be made and the level of customer patronage (Mahmood & Manzoor, 2021; Visnjic, Wiengarten, & Neely, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jönke (2012) concluded that the more customers use the Internet on a regular basis, the more they need and appreciate instant support. Adusei and Tweneboah-Koduah (2019) revealed that after-sales services influenced customer satisfaction in a positive direction so that the level of technical support activities employed by a business organization to a large extent determines the level of profit margin to be made and the level of customer patronage (Mahmood & Manzoor, 2021; Visnjic, Wiengarten, & Neely, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on previous studies on the topic of ISPs, consumer preference for Internet service packages is among the important studies we need to understand (Pan, Ma, & Wu, 2018; Tanford, Baloglu, & Erdem, 2011; Maeng, Kim, & Shin, 2020). These studies reveal that an average of 40% of home Internet consumers switch their service providers annually not only because of price but based on different factors (Mahmood & Manzoor, 2021; Dos Santos & Basso, 2012). These studies also revealed that the level of churn rate for telecommunications industry customers continues to increase by a steady 29% annually.…”
Section: Introductionmentioning
confidence: 99%
“…Service attributes play a pivotal role in influencing consumer decisions and preferences (Chia-Jung & Pei-Chun, 2014;Choi et al, 2020;Nguyen et al, 2019). Understanding attributes is crucial for providers to discern the features and types of services customers are inclined to purchase (Mahmood & Manzoor, 2021). The relationship between the importance of service attributes and customer satisfaction can be dynamic, contingent on performance (Kim et al, 2023;Suryani et al, 2022)…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Internet is considered one of the fundamental pillars for any governmental or private institution to achieve its objectives [1]. With the rapid technological advancements, which lead to short product life cycles and increased competition, it has become imperative for ISP companies to attain and sustain competitive advantages [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate a decline in the importance of criteria related to cost and prices and an increase in the importance of criteria such as quality, reliability, and performance, as evidenced by their repeated mention in the literature. 1 -156…”
Section: Introductionmentioning
confidence: 99%